2019
DOI: 10.3389/fmicb.2019.02447
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Production of the Off-Flavor Geosmin in Tilapia Production in Brazilian Water Reservoirs: Importance of Bacteria in the Intestine and Other Fish-Associated Environments

Abstract: AimTo determine major sources of microbially produced geosmin in the commercially important aquaculture fish species tilapia.Methods and ResultsAbundance and composition of geosmin-producing bacteria in water and fish biosphere (intestine, digesta, and fins) of Nile tilapia (Oreachromis niloticus) raised in net cages in Brazilian freshwater farms were examined. By combining qPCR of the geosmin synthase geoA gene and 16S rRNA gene amplicon sequencing to identify potential geosmin-producing organisms, we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…At the genus level, the gut microbiota was dominated by Cetobacterium , Clostridium_sensu_stricto and Clostridium_XI , which was different from other studies. Lukassen et al [ 56 ] showed Cetobacterium as one of the predominant genera from the intestinal digesta of tilapia from a Brazilian reservoir. The observed discrepancies in microbiota composition may be due to several factors, including rearing environmental conditions, diet composition and genetic lineage.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, the gut microbiota was dominated by Cetobacterium , Clostridium_sensu_stricto and Clostridium_XI , which was different from other studies. Lukassen et al [ 56 ] showed Cetobacterium as one of the predominant genera from the intestinal digesta of tilapia from a Brazilian reservoir. The observed discrepancies in microbiota composition may be due to several factors, including rearing environmental conditions, diet composition and genetic lineage.…”
Section: Discussionmentioning
confidence: 99%
“…), they usually have a terrestrial origin or are present in sediments and foodstuffs. And while they can also be related to some geosmin episodes in aquatic systems, cyanobacteria are still considered the main geosmin producers in freshwater ecosystems (Lukassen et al, 2019;Olsen et al, 2016). The majority of these geosmin-producing cyanobacteria are benthic or epiphytic (70%), while the rest are planktonic (Jüttner and Watson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The immunonutrient could be zinc and the single cell microbe could act like a probiotic and physically block Streptomyces or other producers of geosmin and MIB from being adsorbed into fish. Lukasse et al [181] documented that geosmin mainly enters fish via their guts and proposed that probiotics in fish feeds should block geosmin bioaccumulation. Many probiotic treatments are used in aquaculture to change the microbial communities in animal guts to break down antimetabolites like phytase and to improve immunity [182].…”
Section: Concerns With Arsenic In Aquaculture-an Important Source Of Zincmentioning
confidence: 99%